Historian translating histories: a conversation with Rafe de Crespigny on his translation of Zizhi Tongjian and beyond. Issue 1 (2nd January 2022) - Nie, Wei; Xu, Mingwu; de Crespigny, Rafe
ABSTRACT: Known as the Comprehensive Mirror for Aid in Government, Zizhi Tongjian represents the highest achievement in the history compilation work of Song Dynasty. It contains 294 juan and records 1362 years of Chinese history. For many Europeans, Zizhi Tongjian and its related works provided a preliminary source for them to know and study China and its history since the publication of de Mailla’s works in 1777. The translated versions of Zizhi Tongjian by Rafe de Crespigny are widely accepted for readability and comprehensibility. This interview with the translator tries to unveil the factors that may influence the translation like translator identity, translation intentions and historical context during the translation process.